(3OjhGf Ydj Hf CHj WGdHs - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s ((3YHOGdUeO Hf eMeO GdCUagGfj s)
(3ChdgG (B:s
(3bGd CejQ GdeDefjf hEeGe GdeJbjf(B: (3GdfGS ef Lgg GdJeKGd CcaGA CHhge COe hCege MhGA s
(3BNQgG (B:s
(3hdh cfG EPG eJfG JQcfG dcGf GdehJ QGMI dcd Mj hdcfG EPG eJfG oHYKfG hofSCd HYOg Yf cd TF s
(3OjhGf Ydj Hf CHj WGdHs
(3CfhGQ GdYbhd ef CTYGQ hMqj GdQShd fSNI CNQi efg GfXQgG aj GdLRA GdChd GdbSe GdKGfj aj UaMI (B89 (3COHs
(3fSNI KGfjI Hjf SWhQgG JQLeI HGdaGQSjI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs